Aktivitas Antioksidan Teh Kombinasi Daun Anting-Anting Dan Daun Kelor Dengan Variasi Suhu Pengeringan - Fitriani, Nanik; , Ibu Dra. Aminah Asngad, M. Si; , Endang Setyaningsih, S. Si, M. Si (2016)
Tea combination leaf earring and Moringa leaf is one beverage that has health giving properties that can be potentially as a basic ingredient of making tea. The content of the chemical compound leaf earrings are saponins, tannins, flavonoids and essential oils, while the chemical compound content of Moringa leaves are saponins, tannins, flavonoids, alkaloids, steroids, triterpenoids, and essential oil. The purpose of this study to determine the content and the antioxidant activity of a combination of organoleptic quality tea leaf earrings and moringa leaves to the drying temperature variations. The method used in this study is completely randomized design (CRD) with two factors. Factor 1: Variations combination of leaf earrings : moringa leaves 1: 1 (P1), 2: 1 (P2), 1: 2 (P3) and a factor of 2: Variations in temperature of 45 °C (S1), 50 °C (S2 ), 55 °C (S3). The results showed that the highest antioxidant activity of tea at treatment P1S3 namely 81.4%, and the lowest antioxidant activity of tea at treatment P3S1 ie 13.8%. Combination of organoleptic quality tea leaf earrings and Moringa leaves have a light brown color, bitter taste, aroma rather unpleasant, and acceptance do not like.